A Case Study: Innovation of Technology for Prototyping an Aquaponic Mobile Starter Pack in The TVET Syllabus Use Design Development & Research (DDR) - Rahman, Huzainie Hadi; Basri, Azizul Qayyum B; Awang Zainal, Awangku Zaini; M. Yasir, Ahmad Shah Hizam; Zaini, Khazaila; Hussain, Mohd Amirul; Nelfiyantie, N; Othman, Muhammad Azri (Humanika, 2025)
This study aims to develop a mobile Aquaponics Teaching Aid prototype starter pack for teaching purposes in the Design and Technology course, focusing on rural schools in Selangor, Negeri Sembilan, Melaka, Perak, and Pahang using the Design & Development Research (DDR) model. The implementation involved various measurement techniques, including observations, interviews, and surveys in the first phase. Fuzzy Delphi and Delphi techniques were also used in the second and third phases. A total of 18 experts were involved in the development of this product, including teachers who have served in several schools and university lecturers. The structured research results indicate that the product improvement is highly necessary for the purpose of student development in schools, as well as keeping up with the technological advancements of the present time. This will enable students in rural areas to compete in the exploration of knowledge, especially in the field of aquaponics systems and agriculture.